Comparison of postoperative mucociliary clearance times in patients who had undergone septoplasty with or without tampon application - Çukurova, İbrahim; Yalçın, Yusuf; Kırşen, Hüseyin (ENT Updates, 2012)
Objective: To compare postoperative mucociliary clearance times in patients who had undergone septoplasty operations with or without tampon application. Methods: This study included 46 patients (20 female, 26 male) with nasal deviations. The patients underwent septoplasty operations under local anesthesia. The patients were divided in two groups. In Group 1 (28 patients) Merocell® tampons were packed into two nasal passages for the stabilization of the septum. On postoperative 2nd day tampons were removed, and nasal irrigation was started using saline solution. In Group 2 (18 patients) transeptal sutures were placed for septal stabilization and nasal irrigation with saline solution was started from postoperative 6th hour. All patients had undergone saccharine clearance test before the procedure, and at postoperative 1st week and 3rd month, and the results were compared. Results: Preoperative nasal mucociliary clearance times of 46 patients aged 20 to 53 years were as follows: Group 1: 14.65 min at the side of the septal deviation (deviated side), and 14.07 min at the non-deviated side; In Group 2, the corresponding time intervals were 11.9 vs. 13.1 minutes, respectively. At postoperative 1st week, in Group 1, mucociliary clearance times were 12.54 min for the deviated and 11.23 min for the non-deviated nasal septa. While in Group 2, the corresponding times of clearance were 10.1 vs. 10.8 min. At postoperative 3rd month, in Group 1, mucociliary clearance times were 11.6 min for the deviated and 10.4 min for the non-deviated septa. In Group 2, the corresponding clearance times were 6.76 min vs. 7.8 min. Conclusion: Postoperative mucociliary clearance times of the patients operated for nasal septal deviation were evaluated. We detected shorter mucociliary clearance times in the group operated with suturing technique when compared with the other group.